Analisis Bunyi Bahasa Indonesia: Fonetik Dan Fonemik - Puja Sri Rahayu; Emi Mutiara; Rismayanti Rismayanti (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research uses the method of analyzing language sound phonemes to understand how the sounds of Indonesian are organized in its phonological system. The results are expected to provide in-depth insight into the sound structure of this language, support linguistic understanding and contribute to the development of language teaching methods. This research shows that phonemes in Indonesian have twenty-three consonant sounds and ten vowel sounds. The twenty-three consonant sounds are [p, b, t, d, c, j, k, ˀ, g, m, n, ŋ, ñ, l, f, s, z, ʃ, x, h, r, w, y]. Meanwhile, the ten vowel sounds are [a, i, I, u, U, e, ә, є, o, ↄ]. While the nineteen consonant phonemes, namely /p/, /b/, /t/, /d/, /k/,/l/,/g/,/c/, /j/,/s/, /h/, /m/, /n/, ñ/, /ŋ/,/r/, /R/,/w/, /y/.